Fantástico y ruptura en la poesía española del siglo XXI: una primera aproximación - López Fernández, Álvaro; Molina Gil, Raúl (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
In recent years, theories of the fantastic have been expanding their field of application to include poetry, traditionally excluded from these studies. At present we already have some critical approaches that have focused, above all, on a figurative fantastic poetics based on its narrativity. Without undermining the transgressive potential of these poems, in this article we want to expand this corpus towards more experimental and rupturist poetics, with the aim of demonstrating that there are also fantastic echoes in these more unexplored areas. Thus, after some initial theoretical disquisitions and a review of some of the most interesting narrative poetics in their relationship with the non-mimetic, we will study the fantastic effects caused by compositions by Clara Janés, Antonio Méndez Rubio, Ángela Segovia, Juan Andrés García Román, Xaime Martínez, Ana Correro and Juan Fernández Rivero.
Keywords: contemporary spanish poetry; fantastic; rupture; experimentation; narrativity